ANALISIS KETEPATAN KODE DIAGNOSA OBSTETRI TERHADAP KELANCARAN KLAIM BPJS RS.X KOTA BENGKULU - Heltiani, Nofri; Asroni, Nurwahyu; Suryani, Tri Endah (Politeknik Kesehatan Kemenkes Malang, 2023)
Backgroud: The obstetric code is a code that is more detailed and has differences from other disease codes, so errors often occur in enforcing the code. Based on observations of 10 obstetric claim files submitted to BPJS, it was found that 6 (60%) files were pending due to diagnoses and codes entered on medical resumes that were not in accordance with BPJS, which resulted in delays in the claim payment process to the hospital. This study aims to analyze the accuracy of the obstetrical diagnosis code for the smoothness of BPJS RS.X claims in Bengkulu City.Subjects and Method: This type of research is descriptive with a cross sectional approach. The population in this study were 137 obstetrical claim files for 2021 with a sample of 58 files taken by simple random sampling. The data used in this study were primary and secondary data which were processed univariately.Results: 31(53%) obstetric files smooth BPJS claims and 27(47%) non-current BPJS claim files with details 3(5%) incomplete claim files, 22(38%) incorrect obstetric code and 2(3%) incomplete documentationConclusion: Most of the accuracy of the obstetric diagnosis code experienced smoothness of the BPJS when it was verified by the BPJS verifier.